MENINGKATKAN AKTIVITAS BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN PADA MANUSIA MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING DI KELAS VIIIF MTs NEGERI 1 MERANGIN TAHUN 2020/2021 - Hidayatul Fadliah, S.Pd.I (LP3M | STKIP YPM Bangko, 2022)
This study aims to increase the learning activities of class VIIIF students in the odd semester of MTs Negeri 1 Merangin for the 2020/2021 academic year through the application ofdiscovery learning to the Digestive System material in humans. This research is a Classroom Action Research (CAR) which was carried out in two cycles, with each cycle consisting of planning, implementing actions, observing, and reflecting. The research subjects were students of class VIIIF MTs Negeri 1 Merangin in the 2020/2021 school year. Sources of data are teachers and students. Data collection techniques through observation and interviews, then analyzed using qualitative descriptive. Based on the results of the observation analysis of student learning activities when the science learning process on the human digestive system material obtained a percentage of 68.28% in the first cycle, increasing to 87.28 in the second cycle. Thus obtained the average class results with a percentage of 77.78%. Thus all types of learning activities meet the achievement of good criteria